Effect of sub-optimal moisture levels on the quality of groundnut (Arachis hypogaea L.) during storage in triple-layer hermetic storage bags - Swathi, Y.; Rajanikanth, P.; Jella, Satya Narayana; Mangala, Uppala N.; Adithya, Guntha; Anilkumar, Vemula; Sudini, Hari Kishan (Frontiers in Sustainable Food Systems, 2024)
Storage is an important aspect of groundnut, as the in-shell and shelled kernels are prone to infestation by insects, pests, and fungi. Among several storage pests, the groundnut bruchid, Caryedon serratus, causes serious losses. Farmers often resort to different management practices, including hermetic storage, to control it. The moisture content of the commodity plays an important role in insect infestation during storage. Drying to safe moisture levels before storage is known to prevent the activity of various living organisms, such as storage pests. However, drying to low levels of moisture may not be economical for farmers, as they may not have access to devices to accurately check product moisture. In this regard, we wanted to demonstrate the efficacy of triple-layer hermetic storage bags in preventing the damage caused by C. serratus when the groundnuts are stored at intermediate (10%) and high (14%) levels of moisture compared to traditionally used bags such as polypropylene bags and jute bags. Groundnut pods at 10% moisture content and 14% moisture content were separately inoculated with adult bruchids and a toxigenic strain of Aspergillus flavus fungal inoculum before storing them for 6 months. Results from groundnut samples taken at two-month intervals indicated that groundnut pods stored in triple-layer hermetic bags were completely free from infestation by C. serratus by recording a zero number of eggs laid, number of pupae, adult emergence, percentage of loss, and percentage of damage up to 6 months of storage, by creating low oxygen (hypoxia) and high carbon dioxide (hypercarbia) conditions. Results also indicate no loss of pod weight stored in triple-layer bags, but a slight reduction in germination percentage was recorded due to a slight increase in fungal activity, but the reduction was significantly less in triple-layer plastic bags compared to other bag types. Similarly, biochemical constituents such as oil and protein content were slightly reduced in triple-layer plastic bags when pods were stored at a 10% moisture level, but a higher reduction was observed at a 14% moisture level. However, the reduction was very high and significant in other bag types at both 10 and 14% moisture levels.